Pengaruh Media Puzzle Gambar Seri Terhadap Keterampilan Menulis Karangan Narasi Di Kelas Rendah - Novi Septiani; Iis Nurasiah; Aditia Eska Wardana (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2020)
Based on the results of a literature study that has been carried out at the 5th Cibeureum Hilir Elementary School in the City of Sukabumi. The purpose of this study was to determine the effect of using series picture media puzzles on narrative essay writing skill in low class. This research method is using Quasi Experimental Design with Nonequvalent Control Group Design. sample is used by 40 low grade elementary school student. The result of analysis obtained by score of post test. There is a different on the average score between experiment class and control class that is equal to 77.00 and 68.25. This is has proven with T test of two independent sample and obtained sig. score (2-tailed) equal to 0.018. That sig. score are lower than 0.05 so that H0 was refused and H1 was accepted. The criteria on average score on experiment class and control class was differents significantly. So it can be concluded that there is an influence of using series picture media puzzles on narrative essay writing in low class.